The role of pyroptosis in heart failure and related traditional chinese medicine treatments - Qin, Jie; Yang, Qianhe; Wang, Yan; Shi, Mengdi; Zhao, Xin; Zhou, Yabin (Frontiers in Pharmacology, 2024)
Pyroptosis is a type of programmed cell death that is mediated by both typical and atypical pathways and ultimately leads to the lysis and rupture of cell membranes and the release of proinflammatory factors, triggering an intense inflammatory response. Heart failure (HF) is a serious and terminal stage of various heart diseases. Myocardial hypertrophy, myocardial fibrosis, ventricular remodeling, oxidative stress, the inflammatory response and cardiomyocyte ionic disorders caused by various cardiac diseases are all risk factors for and aggravate HF. Numerous studies have shown that pyroptosis can induce and exacerbate these reactions, causing progression to HF. Therefore, targeting pyroptosis is a promising strategy to treat HF. This paper summarizes the role of pyroptosis in the development of HF and the underlying mechanism involved. Recent research progress on the ability of traditional Chinese medicine (TCM) extracts and formulas to inhibit pyroptosis and treat HF was summarized, and some traditional Chinese medicine extracts and formulas can alleviate different types of HF, including heart failure with preserved ejection fraction (HFpEF), heart failure with reduced ejection fraction (HFrEF), and heart failure with midrange ejection fraction (HFmrEF), by targeting pyroptosis. These findings may provide new ideas and evidence for the treatment or adjuvant treatment of HF by targeting pyroptosis.